COMPARISON OF THE EFFECTIVENESS OF SHIATSU MASSAGE THERAPY AND ABDOMINAL STRETCHING EXERCISE ON REDUCING THE LEVEL OF PRIMARY MENSTRUAL PAIN (DYSMENORRHEA) IN ADOLESCENT GIRLS - Roni Rowawi; Hidayat Wijayanegara; Lina Herlina (Jurnal Ilmiah Keperawatan, 2025)
Background: Menstruation in adolescents is often accompanied by dysmenorrhea, affecting 40–80% and causing discomfort and absenteeism. Non-pharmacological methods like Shiatsu massage and abdominal stretching are effective, safe alternatives to medication.Objective: This study aimed to evaluate the effectiveness of shiatsu massage and abdominal stretching exercises in reducing primary dysmenorrhea among adolescent girls. Methods : A quasi-experimental design with a pre-post test two-group comparison was employed. Sixty-six adolescent girls with primary dysmenorrhea were purposively selected and divided into two groups: one received shiatsu massage therapy, and the other performed abdominal stretching exercises. Data were analyzed using the Wilcoxon and Mann-Whitney tests with a significance level set at p < 0.05. Results : Showed that both interventions significantly reduced menstrual pain (p = 0.000). However, the shiatsu group experienced a greater average pain reduction (2.36 points) compared to the stretching group (1.55 points). Conclusion : The results of this study indicate that shiatsu massage therapy demonstrates a greater effectiveness in alleviating primary menstrual pain, commonly referred to as dysmenorrhea, when compared to abdominal stretching exercises, exhibiting a notable difference of 0.8 points in pain reduction between the two interventions. Suggestion: This intervention can be used in midwifery and healthcare settings, with Shiatsu materials serving as educational tools for adolescents on dysmenorrhea and reproductive health.